2022
DOI: 10.3390/ma15217847
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Permeability Properties of Pervious Concrete Containing Coal Bottom Ash Aggregates

Abstract: This study investigates the strength and permeability properties of pervious concrete-containing coal bottom ash (CBA) aggregates. Two pervious concrete mixtures were fabricated with different aggregate size distributions. One mixture contained CBA aggregates with a single-type distribution and the other mixture contained CBA aggregates with a hybrid-type distribution. The test parameters of the CBA pervious concrete included the water/cement (W/C) ratio and compaction level to investigate their effects on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Cylindrical POC specimens were made using a cylindrical mold with a diameter of 100 mm and a height of 200 mm, while prismatic POC specimens were made using a prismatic mold with dimensions of 100 x 100 x 400 mm 3 . The paste specimens were made using a cylindrical mold with a diameter of 50 mm and a height of 100 mm, and a prismatic mold with dimensions of 40 x 40 x 160 mm 3 . Each type of POC and paste was replicated three times.…”
Section: Creating Test Specimens and Curing Methodsmentioning
confidence: 99%
“…Cylindrical POC specimens were made using a cylindrical mold with a diameter of 100 mm and a height of 200 mm, while prismatic POC specimens were made using a prismatic mold with dimensions of 100 x 100 x 400 mm 3 . The paste specimens were made using a cylindrical mold with a diameter of 50 mm and a height of 100 mm, and a prismatic mold with dimensions of 40 x 40 x 160 mm 3 . Each type of POC and paste was replicated three times.…”
Section: Creating Test Specimens and Curing Methodsmentioning
confidence: 99%
“…There is an abundance of published literature on the characteristics, mechanical properties and durability aspects of PC since this type of concrete has been developed some time ago. For example, there is available literature that addresses plain PC [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] as well as PC that incorporates supplementary cementitious materials [18][19][20][21][22]. However, research on PC that contains RCA as partial or full replacement of NA remains relatively scarce, especially in combination with fibers that are capable of compensating for the inferior properties of the recycled aggregate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mitrosz et al [12] conducted a review on the innovative use of recycled concrete aggregates and rubber particles from waste tires as sustainable alternatives to traditional natural aggregates in part. Park et al [13] studied the characteristics of strength and permeability in pervious concrete that incorporated coal bottom ash aggregates, creating mixes with diverse aggregate size distributions. Anwar et al [14] analyzed the performance of pervious concrete with various substitutes for cement and aggregates, and the results showed that using substitutes is feasible.…”
Section: Introductionmentioning
confidence: 99%